2021
DOI: 10.3892/etm.2021.10340
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 2 deficiency enhances isoflurane-induced spatial cognitive impairment in adult mice by affecting neuroinflammation, neurogenesis and neuroplasticity

Abstract: Isoflurane (Iso) is a commonly used inhalational anesthetic and is associated with the incidence of postoperative cognitive dysfunction (POCD). Cannabinoid receptor 2 (CB2R) was previously reported to have a promising neuroprotective function in cases of POCD, but the specific mechanisms have remained to be fully explored. The aim of the present study was to investigate the effect of CB2R deficiency on spatial cognitive performance in adult mice exposed to Iso. A total of 20 adult CB2R knockout (KO) and 20 wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In the granule cells, expression of the calcium-binding protein, calretinin, is observed between the 2nd and 4th weeks of neurogenesis (Zhao et al 2008). It has been shown that isoflurane or sevoflurane can induce inhibition of neurogenesis in the hippocampus of rodent animals (Jia et al 2020;Li et al 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…In the granule cells, expression of the calcium-binding protein, calretinin, is observed between the 2nd and 4th weeks of neurogenesis (Zhao et al 2008). It has been shown that isoflurane or sevoflurane can induce inhibition of neurogenesis in the hippocampus of rodent animals (Jia et al 2020;Li et al 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…16 HFCS consumption induces neuroinflammation in the hippocampus (3). This is characterized by the expression of pro-inflammatory cytokines and subsequent hippocampal dysfunction including cognitive decline and reduction of neurogenesis (19,20). To investigate the synergistic effect of prenatal and postnatal HFCS intake on the hippocampus, we analyzed the mRNA expression levels of Tnfa, Il1b, and Il6 in the hippocampus of offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Both male and female CB2 –/– mice also show impairments in social memory, however, female CB2 –/– mice have significantly higher levels of synapsin-I immunoreactivity in the hippocampus ( Komorowska-Müller et al, 2021b ), highlighting a need to understand sex-specific differences in CB2 receptor function, an area that is currently under-studied. Additionally, in a model of postoperative cognitive dysfunction (POCD), CB2 –/– mice are more vulnerable to isoflurane (Iso)-induced spatial learning and memory impairments compared to WT mice ( Li et al, 2021 ), again suggesting a key role for CB2 receptors in regulating hippocampal-dependent behaviors. While more studies are needed to elucidate the utility of targeting CB2 receptors in treating schizophrenia, these studies collectively indicate that targeting CB2 receptors may represent a novel mechanism to achieve both antipsychotic and pro-cognitive efficacy.…”
Section: Cannabinoid Type-2 Receptor-mediated Modulation Of Hippocamp...mentioning
confidence: 99%
“…In addition, CB2 appears to play important roles in microglial activation, inflammation, and cognitive disruptions observed following post-operative stress. The expression of CB2 receptors in the hippocampus is upregulated in mice following surgery, and post-operative administration of the CB2 agonist JWH133 can both decrease the expression of pro-inflammatory cytokines and alleviate surgery-induced hippocampal-dependent memory loss ( Sun et al, 2017 ; Li et al, 2021 ). The ability of CB2 receptors to regulate inflammatory processes could have utility in treating numerous diseases including Alzheimer’s disease ( Wu et al, 2013 ), postoperative recovery ( Sun et al, 2017 ), and neuropathic pain ( Cabanero et al, 2020 ).…”
Section: Cannabinoid Type-2 Receptors Expressed On Microglia Regulate...mentioning
confidence: 99%